Ion-electron conduction full-chain network zinc powder anode with bionic skin-capillary structure and preparation method of ion-electron conduction full-chain network zinc powder anode
By constructing an ion-electron conduction network of bionic skin-capillary structure on the zinc powder anode, the instability and retardation of the zinc powder anode are solved, and more efficient Zn2+ transmission and battery performance improvement are achieved.
Patent Information
- Application Number
- CN202411249417.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-31
AI Technical Summary
The zinc powder anode is prone to instability and slow ion diffusion kinetics due to monodispersed structure, and it is easy to have dendrite growth and side reaction problems. The existing technology is difficult to solve the instability of the electrode/electrolyte interface and the slow ion-electron diffusion kinetics simultaneously. The problem.
Using a full-chain network of ion-electron conduction with bionic skin-capillary structure, the surface protective coating and internal ion-electron conduction network are formed on the zinc powder anode, and Kevlar fibers and strong alkaline substances are used to form agitate in DMSO. ANF, then mixed with zinc powder and conductive agent, vacuum filtration to form an electrode bottom layer, and a surface coating of ANF is formed thereon, drying to obtain a zinc powder anode with a bionic skin-capillary structure.
It effectively overcomes the interface instability and dynamic obstacles of zinc powder anode, improves the transmission efficiency and plating/peeling efficiency of Zn2+, extends the cycle life of the battery and improves the rate performance of the battery.
Smart Images

Figure CN119230766A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc metal batteries, and specifically relates to an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure and a preparation method thereof. Background Art
[0002] As a sustainable stationary energy storage system, rechargeable zinc batteries have attracted much attention due to their high safety, low cost and environmental friendliness. Compared with the commonly used zinc foil, zinc powder (ZnP) is considered to be a potential anode material for promoting the development of zinc batteries due to its adjustable shape and easy large-scale processing. However, due to the monodisperse structure, zinc powder anodes face higher instability and sluggish ion diffusion kinetics, as well as discontinuous electron pathways, which are more likely to cause dendrite growth and side reaction problems.
[0003] To address the problems faced by ZnP anodes, various strategies have been developed, such as alloying treatment, electrode structure design, addition of conductive agents and functional binders, etc. Although these methods have made significant progress, there are still challenges in simultaneously solving the problems of electrode / electrolyte interface instability and sluggish ion-electron diffusion kinetics of ZnP anodes. Considering the structural and functional characteristics of ZnP, a multifunctional anode integrating a surface protective coating and an internal ion-electron conduction network will show strong vitality, overcome the interface instability and kinetic barriers, and thus give full play to the advantages of ZnP and realize excellent zinc batteries. Summary of the invention
[0004] The present invention is based on the above background technology and aims to provide an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure and a preparation method thereof.
[0005] The invention provides a method for preparing an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure, which has the following characteristics and comprises the following steps: S10, dissolving Kevlar fiber and a strong alkaline substance in DMSO and stirring until the mixture is dark red to obtain a reaction solution; S20, washing the reaction solution and separating to obtain ANF; S30, adding zinc powder, a conductive agent and ANF into DMSO and stirring evenly, and then vacuum filtering to obtain an electrode bottom layer; S40, vacuum filtering a DMSO dispersion of ANF above the electrode bottom layer, so that a surface coating of ANF material is formed above the electrode bottom layer; S50, drying the electrode bottom layer with the surface coating to obtain an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure.
[0006] The method for preparing the ion-electron conductive full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention may also have the following characteristics: wherein, in step S10, the strong alkaline substance includes an inorganic strong base or an organic strong base.
[0007] In the preparation method of the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention, it can also have the following characteristics: wherein, in step S10, the ratio of the feeding amounts of Kevlar fiber, strong alkaline substance and DMSO is (0.1~0.2)g:(0.1~0.2)g:(50~100)mL.
[0008] The method for preparing the ion-electron conductive full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention may also have the following characteristics: wherein, in step S10, the stirring method is stirring at room temperature for 168h to 192h.
[0009] In the preparation method of the ion-electron conductive full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention, it can also have the following characteristics: wherein, step S20 includes the following sub-steps: S21, using a large amount of H2O and DMSO to wash the reaction solution until the pH is 6 to 8; S22, using DMSO to filter and remove excess water.
[0010] The method for preparing the ion-electron conductive full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention may also have the following characteristics: wherein, in step S30, the conductive agent includes acetylene black or graphite.
[0011] In the preparation method of the ion-electron conductive full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention, the following characteristics can also be provided: wherein, in step S30, the feed mass ratio of zinc powder, conductive agent and ANF is (30-40):(3-5):(0.5-1.5), and the mass of zinc powder in the bottom layer of the electrode is 19 mg / cm by filtration. 2 ~21mg / cm 2 , stirring time is 3h~5h.
[0012] In the preparation method of the ion-electron conductive full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention, the following characteristics can also be provided: wherein, in step S40, the concentration of the DMSO dispersion of ANF is 0.1 mg / mL to 0.4 mg / mL, and the amount of the surface coating of the ANF material is 0.1 mg / cm 2 ~0.5mg / cm 2 .
[0013] In the preparation method of the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure provided by the present invention, it can also have the following characteristics: wherein, in step S50, the drying method is vacuum drying at 70°C to 90°C for 22h to 26h.
[0014] The present invention also provides an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure, which has the following characteristics: it is prepared by any of the aforementioned methods for preparing an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure.
[0015] Functions and Effects of the Invention
[0016] According to the present invention, an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure and a preparation method thereof, firstly, zinc powder, a conductive agent and ANF are used to prepare an ion-electron conduction network (capillary) at the bottom of the electrode, and then a top ANF coating (skin) is prepared thereon to form an ion-electron conduction full-chain network for stabilizing the bionic skin-capillary structure of the zinc powder anode. The protective layer on the surface of the electrode has the functions of ion redistribution and electron blocking, which can effectively homogenize Zn 2+ The capillary-like adhesive extending inward can strongly anchor ZnP and provide high Zn 2+ Selectivity, thereby increasing Zn 2+ Plating / stripping efficiency.
[0017] The multifunctional anode constructed by the present invention, which integrates a surface protective coating and an internal ion-electron conduction network, will exhibit strong vitality, overcome interface instability and kinetic barriers, thereby giving full play to the advantages of ZnP and providing a promising solution for the development of advanced ZnP electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a flowchart of a method for preparing an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to an embodiment of the present invention;
[0019] Figure 2 The cross-sectional scanning electron microscope images of the initial, electroplated and peeled sections of an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure and a common zinc foil as a working electrode in an embodiment of the present invention are compared;
[0020] Figure 3 yes Figure 2 Schematic comparison of the corresponding action mechanism of the ion-electron conduction full-chain network zinc powder anode with bionic skin-capillary structure and ordinary zinc foil when used as working electrode; Figure 4 are the activation energy and ion transfer number of the ion-electron conduction full-chain network zinc powder anode (ZnP-FC electrode) and zinc foil with bionic skin-capillary structure in the test example of the present invention;
[0021] Figure 5 It is a constant current charge-discharge diagram when the symmetrical battery in the test example of the present invention respectively adopts the same ion-electron conduction full-chain network zinc powder anode (ZnP-FC electrode) with a bionic skin-capillary structure and a zinc foil electrode;
[0022] Figure 6 It is a rate performance diagram of a KVOH full battery when the ZnP-FC and zinc foil electrodes constructed in the test example of the present invention are used as negative electrodes respectively;
[0023] Figure 7 It is a long cycle performance diagram of the KVOH full battery when the ZnP-FC and zinc foil electrodes constructed in the test example of the present invention are used as negative electrodes respectively. DETAILED DESCRIPTION
[0024] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments and the accompanying drawings specifically illustrate the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure and the preparation method thereof.
[0025] <Example>
[0026] Figure 1 It is a flowchart of a method for preparing an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to an embodiment of the present invention.
[0027] like Figure 1 As shown, this embodiment provides a method for preparing an ion-electron conductive full-chain network zinc powder anode with a bionic skin-capillary structure, comprising the following steps:
[0028] S10, dissolving 0.1 g of Kevlar fiber and 0.1 g of KOH in 50 mL of DMSO, and stirring at room temperature for 168 h to 192 h until the solution gradually turns dark red to obtain a reaction solution.
[0029] S20, separating and obtaining ANF, comprises the following sub-steps:
[0030] S21, washing the reaction solution with a large amount of H2O and DMSO until the pH reaches 7 to obtain ANF;
[0031] S22, remove excess water in ANF by filtration using DMSO.
[0032] S30, 36 g of zinc powder, 4 g of acetylene black and 1 g of ANF were added to 30 mL of DMSO and stirred for 3 h to 5 h, and then vacuum filtered to obtain the bottom layer of the full-chain electrode, which was recorded as the electrode bottom layer.
[0033] In this step, the mass of zinc powder in the bottom layer of the electrode was controlled to be 19 mg / cm during vacuum filtration. 2 ~21mg / cm 2 .
[0034] S40, dispersing the ANF obtained in step S22 in DMSO at a concentration of 0.2 mg / mL, and then vacuum filtering the dispersion on the electrode bottom layer obtained in step S30, thereby forming a surface coating of ANF material on the electrode bottom layer.
[0035] In this step, the amount of surface coating of the ANF material was controlled to be 0.125 mg / cm during vacuum filtration. 2 .
[0036] S50, vacuum drying the electrode bottom layer with the surface coating at 70°C to 90°C for 22h to 26h to obtain an ion-electron conductive full-chain network zinc powder anode (ZnP-FC electrode) with a bionic skin-capillary structure.
[0037] This embodiment also provides an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure, which is prepared by the preparation method of the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure provided in this embodiment.
[0038] Figure 2 The cross-sectional scanning electron microscope images of the initial, electroplated and peeled sections of an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure and a common zinc foil as a working electrode in an embodiment of the present invention are compared; Figure 3 yes Figure 2 Comparison of the corresponding schematic diagrams of the working mechanisms of the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure and ordinary zinc foil when used as working electrodes.
[0039] like Figures 2-3 As shown in the figure, in the primary cell, due to the direct contact between the zinc foil and the electrolyte, the reaction site is insufficient, and obvious dendrites and by-products are produced on the surface of the zinc foil electrode, which will inevitably lead to Zn 2+ Uneven concentration and Zn 2+The diffusion dynamics are slow; thanks to the ion-electron conduction full-chain network of the bionic skin-capillary structure, the zinc powder anode (ZnP-FC electrode) with the ion-electron conduction full-chain network of the bionic skin-capillary structure effectively inhibits the formation of zinc dendrites and by-products, making the internal network of the electrode tightly interwoven and the electrode surface smooth.
[0040] <Test example>
[0041] This test example conducts an electrochemical test on the ion-electron conduction full-chain network zinc powder anode (ZnP-FC electrode) with a bionic skin-capillary structure in the embodiment, and the test process is as follows:
[0042] Symmetrical cells and full cells were prepared using a CR2032 battery shell device, 2.0 M ZnSO4 as the electrolyte, and GE-Whatman glass fiber as the separator.
[0043] Among them, the symmetrical battery uses two identical ZnP-FC or zinc foil as electrodes; the full battery uses ZnP-FC or zinc foil electrode as the negative electrode, KV 12 O 30-y nH2O (KVOH) as the positive electrode.
[0044] The preparation method of the above-mentioned KVOH positive electrode includes the following steps: (1) dissolving 0.07g of K2SO4 and 0.27g of V2O5 in 60mL of deionized water, then dropping 1.5mL of 30wt% H2O2, stirring continuously for 0.5h, and then transferring the solution to a 100mL Teflon autoclave for hydrothermal reaction at 120°C for 12h. The product is washed with H2O and then vacuum dried at 80°C for 12h to obtain KVOH; (2) KVOH, acetylene black and polytetrafluoroethylene are fully stirred in N-methylpyrrolidone at a mass ratio of 8:1:1 to form a uniform slurry. The obtained slurry is uniformly cast on the surface of titanium foil, and vacuum dried at 80°C for 24h to obtain the KVOH positive electrode. Among them, the loading mass of KVOH on the surface of titanium foil is controlled to be 4mg / cm 2 .
[0045] After preparing the KVOH positive electrode, the energy storage performance of the symmetric battery and the full battery was tested using a CHI660E electrochemical workstation.
[0046] Figure 4 It is the activation energy and ion transfer number of the ion-electron conduction full-chain network zinc powder anode (ZnP-FC electrode) and zinc foil with bionic skin-capillary structure in the test example of the present invention.
[0047] like Figure 4As shown in Figure 2, compared with zinc foil, ZnP-FC has lower activation energy and higher ion transfer number, indicating that the ZnP-FC electrode with bionic network has more efficient Zn 2+ transmission efficiency.
[0048] Figure 5 It is a constant current charge and discharge diagram when the symmetrical battery in the test example of the present invention respectively adopts the same ion-electron conduction full-chain network zinc powder anode (ZnP-FC electrode) with bionic skin-capillary structure and zinc foil electrode.
[0049] like Figure 5 As shown in the figure, the ZnP-FC||ZnP-FC symmetric battery assembled in this test example is 2 At the current density, a remarkable cycle life of more than 1650 h was obtained.
[0050] Figure 6 It is a rate performance diagram of a KVOH full battery when the ZnP-FC and zinc foil electrodes constructed in the test example of the present invention are used as negative electrodes respectively.
[0051] like Figure 6 As shown, the ZnP-FC||KV assembled in this embodiment 12 O 30-y nH2O has high rate capability (15A / g).
[0052] Figure 7 It is a long cycle performance diagram of the KVOH full battery when the ZnP-FC and zinc foil electrodes constructed in the test example of the present invention are used as negative electrodes respectively.
[0053] like Figure 7 As shown, the ZnP-FC||KV assembled in this embodiment 12 O 30-y nH2O has ultra-long cycle stability (6000 cycles) at a current density of 5 A / g.
[0054] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing an ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure, characterized in that: The following steps are involved: S10, dissolving Kevlar fiber and a strong alkaline substance in DMSO and stirring until the mixture turns dark red to obtain a reaction solution; S20, washing the reaction solution and separating to obtain ANF; S30, zinc powder, conductive agent and ANF are put into DMSO and stirred evenly, and then vacuum filtered to obtain the electrode bottom layer; S40, vacuum filtering the DMSO dispersion of ANF above the bottom layer of the electrode, so that a surface coating of ANF material is formed above the bottom layer of the electrode; S50, drying the electrode bottom layer with the surface coating to obtain the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure.
2. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, In step S10, the strong alkaline substance includes an inorganic strong base or an organic strong base.
3. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, In step S10, the ratio of the amount of the Kevlar fiber, the strong alkaline substance and DMSO is (0.1-0.2) g: (0.1-0.2) g: (50-100) mL.
4. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, In step S10, the stirring method is stirring at room temperature for 168 h to 192 h.
5. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, Step S20 includes the following sub-steps: S21, washing the reaction solution with a large amount of H2O and DMSO until the pH is 6 to 8; S22, remove excess water by filtration using DMSO.
6. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, In step S30, the conductive agent includes acetylene black or graphite.
7. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, In step S30, the mass ratio of the zinc powder, the conductive agent and the ANF is (30-40):(3-5):(0.5-1.5), The mass of the zinc powder in the bottom layer of the electrode was 19 mg / cm 2 ~21mg / cm 2 , The stirring time is 3h to 5h.
8. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, In step S40, the concentration of the DMSO dispersion of ANF is 0.1 mg / mL to 0.4 mg / mL. The amount of surface coating of ANF material is 0.1mg / cm 2 ~0.5mg / cm 2 .
9. The method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure according to claim 1, characterized in that: in, In step S50, the drying method is vacuum drying at 70°C to 90°C for 22h to 26h.
10. An ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure, characterized in that: The zinc powder anode is prepared by the method for preparing the ion-electron conduction full-chain network zinc powder anode with a bionic skin-capillary structure as described in any one of claims 1 to 9.
